Gender-specific design and effectiveness of non-pharmacological interventions against cognitive decline and dementia–protocol for a systematic review and meta-analysis - Zuelke AE; Riedel-Heller SG; Wittmann F; Pabst A; Roehr S; Luppa M (Public Library of Science (PLoS), 2021)
Introduction Dementia is a public health priority with projected increases in the number of people living with dementia worldwide. Prevention constitutes a promising strategy to counter the dementia epidemic, and an increasing number of lifestyle interventions has been launched aiming at reducing risk of cognitive decline and dementia. Gender differences regarding various modifiable risk factors for dementia have been reported, however, evidence on gender-specific design and effectiveness of lifestyle trials is lacking. Therefore, we aim to systematically review evidence on gender-specific design and effectiveness of trials targeting cognitive decline and dementia. Methods and analysis We will conduct a systematic review in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Databases MEDLINE (PubMed interface), PsycINFO, Web of Science Core Collection, Cochrane Central Register of Controlled Trials (CENTRAL) and ALOIS will be searched for eligible studies using a predefined strategy, complemented by searches in clinical trials registers and Google for grey literature. Studies assessing cognitive function (overall measure or specific subdomains) as outcome in dementia-free adults will be included, with analyses stratified by level of cognitive functioning at baseline: a) cognitively healthy b) subjective cognitive decline 3) mild cognitive impairment. Two reviewers will independently evaluate eligible studies, extract data and determine methodological quality using the Scottish Intercollegiate Guidelines Network (SIGN)-criteria. If sufficient data with regards to quality and quantity are available, a meta-analysis will be conducted. Ethics and dissemination No ethical approval will be required as no primary data will be collected. PROSPERO registration number CRD42021235281.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognitive Dysfunction; Dementia; Female; Guidelines as Topic; Humans; Male; Middle Aged; Randomized Controlled Trials as Topic; Risk Factors; Risk Reduction Behavior; Sex Characteristics